Association of CASP8 rs3834129 and CTGF rs6918698 genotypes with susceptibility to colorectal cancer in a Mexican population: CASP8 and CTGF variants are associated with colorectal cancer - Saucedo-Sariñana, Anilú Margarita; Trujillo-Fernández, Yuri Giovanna Vanessa; Juarez-Vázquez, Clara Ibet; Godínez-Rodríguez, Miriam Yadira; Tovar-Jácome, César de Jesús; Barros-NúñeZ, Patricio; Pineda-Razo, Tomás Daniel; Marín-Contreras, María Eugenia; Rosales-Reynoso, Mónica Alejandra (Cellular and Molecular Biology, 2024)
Connective tissue growth factor (CTGF) and Caspase 8 (CASP8) have been implicated in cancer development and progression. Variants such as CASP8 rs3834129 (-652 6N I/D) and CTGF rs6918698 (-945 C>G) have been associated with several cancers, although their association is still debated between populations. This study investigates the possible association between the CASP8 rs3834129 and CTGF rs6918698 variants with colorectal cancer (CRC) in Mexican patients. Genomic DNA was extracted from 250 CRC patients and 250 control subjects. The identification of CASP8 and CTGF variants was performed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) methodology. The association was determined by the odds ratio (OR) analysis and P values were adjusted by the Bonferroni correction. Patients carrying the D/D genotype for the CASP8 rs3834129 variant exhibited an increased susceptibility to CRC (P = 0.012). The D/D genotype was associated with older 50-year-old patients (P = 0.006). In addition, this same D/D genotype was associated with TNM II stage (P = 0.013) and rectal localization (P = 0.023). Additionally, patients carrying the G/G genotype for the CTGF rs6918698 variant showed a decreased susceptibility to CRC (P = 0.009), and in the sex stratification, this gene has protective role in males (P = 0.008). This same genotype was associated with decreased susceptibility to early TNM stages (I+II) (P = 0.023) and right-sided colon tumor localization (P = 0.002). There was no association between response to treatment and the variants analyzed. Our findings suggest that the CASP8 rs3834129 and CTGF rs6918698 variants have a significant impact on the development of CRC.